Strumenti per una medicina del nostro tempo Medicina narrativa, Metodologia Pedagogia dei Genitori e International Classification of Functioning (ICF) - Garrino, Lorenza (Strumenti per la didattica e la ricerca, 2015)
The contribution provided by this publication represents an innovative initiative in the field of training for projects to improve the quality of care. The need for theoretical models, tools and methodologies that favour the participation of the person and their family in care is becoming more and more evident. The synergy between Narrative Medicine, Parent Pedagogy Methodology and ICF allows to give value to patients' stories and experiences, to parenting educational skills within the school, health and family educational pact with a focus on the degree of functioning of the person, be it in condition of health or illness. In this new perspective, the treatment actions aim to establish a relationship of trust that is no longer based on an uncritical adherence to acquired and undisputed knowledge or actions, but on a participation that takes into account the contextual, concrete, daily skills of the citizen an the formalised, general and specific skills of the carers.